Association of Vitamin-D Status with Ischemic Stroke and It’s Risk Factors In Bangladeshi Patients: A Case-Control Study - Chowdhury, Md Abu Hanif; Ahmed, Sahed Uddin; Abedin, Md Jaber; Chowdhury, Md Raihan; Rahman, Aminur; Paul, Sujat; Dutta, Asok Kumar (Bangladesh Journal of Medicine, 2023)
Background: Vitamin D (VD) shortage and inadequacy are serious global health issues affecting people of all ages. Several studies have shown a link between VD insufficiency and ischemic stroke. Unfortunately, VD is rarely measured, diagnosed, or treated, especially in patients with severe neurological disorders like stroke in our context. The study aimed to explore the association between VD and the risk of acute ischemic stroke along with its risk factors in Bangladeshi patients. Methods: Forty-four patients with ischemic stroke and 44 age and sex-matched healthy subjects were included in this study from Chittagong Medical College Hospital. Demographic and clinical data were collected with a structured interview questionnaire. Fasting 25(OH) VD, calcium, lipid profile, and blood sugar were measured. VD levels classified the individuals in sufficient (VDSe”30.0 ng/mL), insufficient (VDI: 20.0–29.9 ng/mL), and deficient (VDD<20.0 ng/mL) status. Results: Out of 44 stroke patients, 27 (61.4%) were men, and the mean age was 54.6±11.0 years (age range: 18-70 years). The frequency of hypertension, diabetes mellitus, obesity, and dyslipidemia were 68.2%, 31.8%, 52.3%, and 81%, respectively, among stroke cases. VDD and VDI was observed in 29 (65.9%), 9 (20.5%) stroke patients and 5 (11.4%), 12 (27.3%) controls respectively. Multiple logistic regression analysis showed an independent association of 25(OH)D deficiency or insufficiency with ischemic stroke (odds ratio: 10.71, 95% confidence interval: 2.21-51.88, p=0.003). Conclusions: This study shows that low VD levels may be associated with an increased risk of ischemic stroke. Bangladesh J Medicine 2023; 34(2): 105-111